1996
DOI: 10.1007/bf00328454
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of genotype, nutrient availability and type of tissue damage on the compensatory response of Salix planifolia ssp. planifolia to simulated herbivory

Abstract: Plant responses to herbivory include tolerance (i.e. compensatory growth) and defense. Several factors influence the tolerance of a plant following herbivory, including plant genetic identity, site nutrient availability, and previous and/or concurrent herbivory. We studied the effects of these factors on the compensatory response of Salix planifolia ssp. planifolia, a shrub species common in the boreal and subarctic regions of North America. We cloned several genets of S. planifolia and submitted them to simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
66
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 46 publications
7
66
0
1
Order By: Relevance
“…A central goal in ecology is to understand and predict the outcomes of these complex species interactions (Morris et al 2007). In some cases, the effects of multispecies interactions on host fitness will be additive and predictable from pairwise effects (Houle and Simard 1996;Maron 1998). However, in other cases, multispecies interactions are non-additive, and quantifying pairwise interactions is insufficient to predict the results of complex interactions (Wootton 1993).…”
Section: Introductionmentioning
confidence: 97%
“…A central goal in ecology is to understand and predict the outcomes of these complex species interactions (Morris et al 2007). In some cases, the effects of multispecies interactions on host fitness will be additive and predictable from pairwise effects (Houle and Simard 1996;Maron 1998). However, in other cases, multispecies interactions are non-additive, and quantifying pairwise interactions is insufficient to predict the results of complex interactions (Wootton 1993).…”
Section: Introductionmentioning
confidence: 97%
“…The availability of resources necessary for compensation may be depressed by competition from neighbouring plants (Dirzo, 1984;Price, 1991, Houle & Simard, 1996, thereby restricting plant regrowth and reproductive compensation (Coley et al, 1985;Maschinski & Whitham, 1989;Price, 1991;Belsky et al, 1993;HjaK lteH n et al, 1993;Sadras, 1996). Moreover, lowproductive habitats, like deserts, constrain the ability of plants to regrow after damage (Rosenthal & Kotanen, 1994;Strauss & Agrawal, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Many extrinsic factors influence a plant's ability to compensate for damage (Maschinski & Whitham, 1989;Houle & Simard, 1996). The availability of resources necessary for compensation may be depressed by competition from neighbouring plants (Dirzo, 1984;Price, 1991, Houle & Simard, 1996, thereby restricting plant regrowth and reproductive compensation (Coley et al, 1985;Maschinski & Whitham, 1989;Price, 1991;Belsky et al, 1993;HjaK lteH n et al, 1993;Sadras, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The tolerance is also related to other environmental factors, such as damage frequency and severity (Houle & Simard 1996, Wise & Abrahamson 2005, Pinkard et al 2007). Stevens et al (2008) reported a positive correlation of aspen tolerance with the proportion of biomass in stems under low-nutrient conditions and no defoliation event; however, it was correlated with greater allocation to stems under high-nutrient conditions and defoliation event.…”
Section: Introductionmentioning
confidence: 99%